Impurity effective mass in superfluid ⁴He - Vakarchuk, I.O.; Babin, V.V. (Condensed Matter Physics, 1998)
The system of bose liquid + impurity is considered. The energy spectrum,
as well as effective mass of impurity is calculated. For the case of an ³He
atom in superfluid <⁴He numerical calculations are performed. Розглядається система “бозе-рідина + домішка”. Розраховано енергетичний спектр домішки та її ефективну масу. Проведено числові розрахунки для випадку атома ³He в рідкому ⁴He.